2011
DOI: 10.1007/s10103-011-0955-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy (LLLT) in human progressive-intensity running: effects on exercise performance, skeletal muscle status, and oxidative stress

Abstract: The aim of this work was to evaluate the effects of low-level laser therapy (LLLT) on exercise performance, oxidative stress, and muscle status in humans. A randomized double-blind placebo-controlled crossover trial was performed with 22 untrained male volunteers. LLLT (810 nm, 200 mW, 30 J in each site, 30 s of irradiation in each site) using a multi-diode cluster (with five spots - 6 J from each spot) at 12 sites of each lower limb (six in quadriceps, four in hamstrings, and two in gastrocnemius) was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
177
4
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(203 citation statements)
references
References 24 publications
16
177
4
6
Order By: Relevance
“…However, previous studies reported better defenses against oxidative stress [16] if LLLT is applied over muscles after intense exercises as well as before exercise as reported in a previous clinical trial [40]. As mentioned above, the main chromophore, or red/NIR light-sensitive protein, present in biological tissues is Cox [5].…”
Section: Discussionmentioning
confidence: 75%
“…However, previous studies reported better defenses against oxidative stress [16] if LLLT is applied over muscles after intense exercises as well as before exercise as reported in a previous clinical trial [40]. As mentioned above, the main chromophore, or red/NIR light-sensitive protein, present in biological tissues is Cox [5].…”
Section: Discussionmentioning
confidence: 75%
“…The LLLT is an important and effective tool, which interacts with biological tissue, produces various physiological and therapeutic effects, including improving muscle performance in both animal 15,25 and human studies 17 . Because of all these effects and by increasing cellular metabolism, when the LLLT penetrate the tissue, could interfere on the movement control and postural stability, improving balance and position sense, which is given by the mechanical stimulation of the muscles and joints.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the LLLT is a widely used resource, it is in constant process of evaluating its various parameters and it needs more controlled studies to confirm their mechanisms of action in the various fields. The use of a single LLLT session has been used to assess their effects on endurance 16 , muscle performance, oxidative stress and fatigue 17 , however note that the use of only a therapeutic session is considered a limitation of this study, and that further studies could assess whether the sum therapies could significantly influence proprioception in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers 22,23 have shown an increase in performance levels with the use of PBMT during progressive cardiopulmonary exercise tests. However, different PBMT devices result in different effects even with the use of similar exercise protocols to induce fatigue, [22][23][24][25] which makes it difficult for clinicians to determine which device should be used.…”
mentioning
confidence: 99%